Molecular characterization of the lam locus and sequences involved in regulation by the AmdR protein of Aspergillus nidulans. - Richardson, I B (1992)
The lam locus of Aspergillus nidulans consists of two divergently transcribed genes, lamA and lamB, involved in the utilization of lactams such as 2-pyrrolidinone. Both genes are under the control of the positive regulatory gene amdR and are subject to carbon and nitrogen metabolite repression. The lamB gene and the region between the two genes have been sequenced, and the start points of transcription have been determined. Within the lam locus are two sequences with homology to elements, required for AmdR regulation, found in the 5' regions of the coregulated genes amdS and gatA. In vitro and in vivo assays were used to investigate the lam and gatA regulatory elements. One of the three gatA elements and one of the two lam elements were shown to bind AmdR protein in vivo and activate transcription. With a gel shift mobility assay, in vitro binding of AmdR protein to the functional gatA element was detected. Both the functional gatA and lam boxes contain within them a CAAT sequence. In vitro binding analysis indicates that a CCAAT-specific factor(s) binds at these sequences, adjacent to or overlapping the AmdR protein-binding site.